2020
DOI: 10.3390/cells9061427
|View full text |Cite
|
Sign up to set email alerts
|

The Role of GSK-3 in Cancer Immunotherapy: GSK-3 Inhibitors as a New Frontier in Cancer Treatment

Abstract: The serine/threonine kinase glycogen synthase kinase-3 (GSK-3) was initially identified because of its key role in the regulation of glycogen synthesis. However, it is now well-established that GSK-3 performs critical functions in many cellular processes, such as apoptosis, tumor growth, cell invasion, and metastasis. Aberrant GSK-3 activity has been associated with many human diseases, including cancer, highlighting its potential therapeutic relevance as a target for anticancer therapy. Recently, newly emergi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 103 publications
0
70
0
Order By: Relevance
“…We and others have found that natural compounds and their derivatives are potential drugs to kill cancer stem cells through GSK3β inhibition [ 67 , 68 ]. It is important to note that GSK3 inhibitors represent also interesting therapeutic tools to restore normal niche functions [ 69 ]. Thus, targeting both stem cells and their niche is crucial to restore physiological tissue regeneration ( Figure 6 ).…”
Section: Gsk3β As a Target For Precision Medicinementioning
confidence: 99%
“…We and others have found that natural compounds and their derivatives are potential drugs to kill cancer stem cells through GSK3β inhibition [ 67 , 68 ]. It is important to note that GSK3 inhibitors represent also interesting therapeutic tools to restore normal niche functions [ 69 ]. Thus, targeting both stem cells and their niche is crucial to restore physiological tissue regeneration ( Figure 6 ).…”
Section: Gsk3β As a Target For Precision Medicinementioning
confidence: 99%
“…Feeder cells expressing HLA-E have been used to enrich for NKG2C + adaptive NK cells [ 98 ] yet it is unclear if the NKG2C + NK cells are significantly expanding or rather it is the lack of NKG2A + NK cells expanding due to inhibition through HLA-E. Another method to enhance expansion of adaptive NK cells involves the addition of the GSK3 inhibitor CHIR99021 to a feeder-free, IL-15 culture protocol [ 101 ]. GSK3 is a constitutively active serine-threonine kinase originally identified for its role in glucose metabolism, however has since been recognized in cell differentiation, survival and immune responses [ 102 ]. How GSK3 inhibition promotes the expansion of adaptive NK cells is unclear.…”
Section: Current Status On the Role Of Adaptive Nk Cells In Cancermentioning
confidence: 99%
“…After understanding their intracellular interactions, GSK3 inhibitors have been researched in the treatment of cancer ( 34 ). Many types of drugs have been developed ( 35 ) and are being tested in pre-clinical and phase I studies, with promising results ( 36 ).…”
Section: Discussionmentioning
confidence: 99%